Modeling Obsessive Beliefs Based on Parenting Styles and Inferential Confusion with the Mediating Role of Fear of Self - Haddadi, Maryam; Khosravi, Sadrollah; Zakeri, Hamidreza (Mental Health and Lifestyle Journal, 2025)
Obsessive beliefs are among the most important cognitive components in explaining and maintaining obsessive–compulsive disorder (OCD) and are influenced by various cognitive, emotional, and environmental factors. The present study aimed to model obsessive beliefs based on parenting styles and inferential confusion with the mediating role of fear of self. This study employed a descriptive–correlational design using structural equation modeling. The statistical population included all patients diagnosed with OCD who referred to psychology and psychiatry clinics in Shiraz, whose diagnosis had been confirmed by psychiatrists and psychologists in 2024. A total of 130 participants were selected through convenience sampling and responded to the Obsessive Beliefs Questionnaire (OBQ-44), Inferential Confusion Questionnaire–Expanded (ICQ-E), Fear of Self scale, and Parenting Styles questionnaire. Data were analyzed using SPSS version 24 and AMOS version 26. Path analysis indicated that authoritarian and permissive parenting styles as well as inferential confusion directly predicted obsessive beliefs, and fear of self significantly mediated these relationships. These findings highlight that fear of self can either facilitate or intensify the impact of cognitive and environmental factors on the formation of obsessive beliefs. The results may be applied in designing cognitive–emotional interventions and in reconsidering parenting styles for the prevention and treatment of OCD.